An all-inorganic quasi-homogenous polyoxometalate/[Mo3S13]2− system for efficient and stable photocatalytic H2 evolution. Issue 9 (7th January 2021) - Li, Wenbo; Min, Shixiong; Wang, Fang; Zhang, Zhengguo; Gao, Dawei
Abstract : An all-inorganic quasi-homogenous photocatalytic system employing a polyoxometalate as the photosensitizer and [Mo3 S13 ] 2− as the catalyst exhibits high activity and stability for H2 evolution. Abstract : An all-inorganic quasi-homogenous photocatalytic H2 evolution system has been developed employing Keggin-type polyoxometalate H4 SiW12 O40 (SiW12 ) as the photosensitizer and [Mo3 S13 ] 2− clusters as the catalyst. This SiW12 /[Mo3 S13 ] 2− system achieves a high turnover number (TON) of 922 based on the [Mo3 S13 ] 2− catalyst in 5 h of reaction and excellent H2 evolution stability for 40 h with a high turnover number of 6876.